Quo Vadis: Anthropological Dimension of the Modern Civilization Crisis - V. M. Shapoval; I. V. Tolstov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the article is the analysis of the causes of the systemic crisis that hit modern civilization through the description of its main structures, identifying the relationship between its elements, assessments of their heuristic potential. This will open up opportunities for finding ways to resolve this crisis, new directions of civilizational development. Theoretical basis of the research are the systems analysis, socio-philosophical and philosophical-anthropological approaches as well as the analysis of scientific developments in the field of global studies. Originality lies in the fact that this article is the first to show the connection between the main structural elements of human civilization as a system. Change in one of the parameters leads to a change in all the others, together with a change in civilization as a whole. Conclusions. The reason for the deep crisis that hit modern civilization is its imbalance as a system. The most important elements of this system are population size, resources and technology, and the core is consciousness in its individual and collective forms. The perception, processing, and use of information, which is a defining civilizational resource, as well as the stability of the entire system depend on the state of consciousness. Consciousness, based on old, obsolete principles and stereotypes, is unable to cope with the most acute challenges of time. New consciousness, since it is formed, will mark the transition to a new theoretical picture of the world and a model of human behavior, in which people will act, driven by proven knowledge, and not willfulness and prejudice. The idea of forming a productive information environment where the ideas of constructiveness and creative work will dominate rather than consumerism and destruction, as is the case at present, must become the categorical imperative of the new consciousness.